Functional TSPO polymorphism predicts variance in the diurnal cortisol rhythm in bipolar disorder. (March 2018) - Prossin, Alan R.; Chandler, Matthew; Ryan, Kelly A.; Saunders, Erika F.; Kamali, Masoud; Papadopoulos, Vassilios; Zöllner, Sebastian; Dantzer, Robert; McInnis, Melvin G.
Highlights: Structural changes to the TSPO protein can occur with a common, functional, single nucleotide polymorphism (rs6971). Structural changes to the TSPO protein may be clinically impactful in humans suffering with bipolar disorder (BD), a stress exacerbated illness. Inter-individual variation in cortisol's diurnal rhythm may be partially explained by this common TSPO polymorphism (rs6971). Presence of common, functional, TSPO polymorphisms may contribute to co-morbidity of stress-exacerbated illnesses in Bipolar Disorder. Abstract: Introduction: Psychosocial stress contributes to onset/exacerbation of mood episodes and alcohol use, suggesting dysregulated diurnal cortisol rhythms underlie episodic exacerbations in Bipolar Disorder (BD). However, mechanisms underlying dysregulated HPA rhythms in BD and alcohol use disorders (AUD) are understudied. Knowledge of associated variance factors have great clinical translational potential by facilitating development of strategies to reduce stress-related relapse in BD and AUD. Evidence suggests structural changes to mitochondrial translocator protein (TSPO) (a regulator of steroid synthesis) due to the single nucleotide polymorphism rs6971, may explain much of this variance. However, whether rs6971 is associated with abnormal HPA rhythms and clinical exacerbation in humans is unknown. Methods: To show this common TSPO polymorphism impacts HPA rhythms in BD, we tested whether rs6971 (dichotomized: presence/absence of polymorphism) predicted variance in diurnal cortisol rhythm (saliva: morning and evening for 3 days) in 107 BD (50 with and 57 without AUD) and 28 healthy volunteers of similar age and ethno-demographic distribution. Results: Repeated measures ANOVA confirmed effects BD (F5, 525  = 3.0, p = 0.010) and AUD (F5, 525  = 2.9, p = 0.012), but not TSPO polymorphism (p > 0.05). Interactions were confirmed for TSPO × BD (F5, 525  = 3.9, p = 0.002) and for TSPO × AUD (F5, 525  = 2.8, p = 0.017). Discussion: We identified differences in diurnal cortisol rhythm depending on presence/absence of common TSPO polymorphism in BD volunteers with or without AUD and healthy volunteers. These results have wide ranging implications but further validation is needed prior to optimal clinical translation.